2016
DOI: 10.1371/journal.pone.0166436
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated Respiratory Motor Activity in Nerves Innervating the Upper Airway Muscles in Rats

Abstract: Maintaining the patency of the upper airway during breathing is of vital importance. The activity of various muscles is related to the patency of the upper airway. In the present study, we examined the respiratory motor activity in the efferent nerves innervating the upper airway muscles to determine the movements of the upper airway during respiration under normocapnic conditions (pH = 7.4) and in hypercapnic acidosis (pH = 7.2). Experiments were performed on arterially perfused decerebrate rats aged between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…2). Similarly, Tachikawa et al found that the discharge frequency of the RLN synchronized with that of the PN whether in a normocapnic condition or hypercapnic acidosis, 26 and other studies found that RLN-innervated muscles contracted simultaneously with the abdominal muscles during forced expiration, such as when coughing. 7,24 In addition, we showed that most of the fibers in the RLN are motor fibers using AChE staining, even though the number of motor fibers in the RLN was much less than that in the PN (Fig.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…2). Similarly, Tachikawa et al found that the discharge frequency of the RLN synchronized with that of the PN whether in a normocapnic condition or hypercapnic acidosis, 26 and other studies found that RLN-innervated muscles contracted simultaneously with the abdominal muscles during forced expiration, such as when coughing. 7,24 In addition, we showed that most of the fibers in the RLN are motor fibers using AChE staining, even though the number of motor fibers in the RLN was much less than that in the PN (Fig.…”
Section: Discussionmentioning
confidence: 81%
“…1 Tachikawa et al found that the discharge frequency of the RLN synchronized with that of the PN, and this demonstrated the theoretical possibility of reestablishing autonomic and physiological respiration with RLN-PN anastomosis. 26 Gauthier et al found that spontaneous discharge from an anastomosed PN could be detected even after complete transection of the spinal cord at the C2 level in a rat model. 12 Using a rabbit model, Derrey et al studied the effect of anastomosis of the inferior laryngeal nerve (ILN) to the PN and found poor neurogenic electrical activity of the diaphragm.…”
mentioning
confidence: 99%
“…In such preparations, respiratory rhythms (19) and firing patterns of the medullary respiratory neurons (20) are similar to those of adult in vivo mammal preparations. Thus, we used this experimental model to examine respiratory motor activity during normo-and hypercapnia in efferent nerves innervating the upper airway muscles, such as the HGN innervating the tongue; the first, second, and third cervical spinal nerves (CN) innervating the infrahyoid muscles; the external branch of the superior laryngeal nerve (SLN) innervating the cricothyroid and inferior pharyngeal constrictor muscles; and the recurrent laryngeal nerve (RLN) innervating the laryngeal abductors and laryngeal adductors (21).…”
Section: Respiratory Hypoglossal Nerve Activity Coordinated With Motomentioning
confidence: 99%
“…Under normocapnic conditions (5% CO 2 ), stable inspiratory activity of the phrenic nerve (PN)-which innervates the main inspiratory muscle, the diaphragmspontaneously occurs at a frequency of ≈0.3 Hz in the perfused preparations (21). The integrated PN activity exhibited an augmenting pattern ( Fig.…”
Section: Respiratory Hypoglossal Nerve Activity Coordinated With Motomentioning
confidence: 99%